(untitled) (Journal of actual problems of jurisprudence, 2025)
In this article, a study is conducted on the interaction of intellectual property law with branches of private law. In particular, the interaction of intellectual property law with civil law is substantiated. Intellectual property law acts as a sub-branch of civil law, respectively, the subject of legal regulation also consists of property and personal non-property relations that develop with respect to intellectual property objects. In turn, the exclusive right to intellectual property belongs to the category of property rights, and as a subjective right is one of the objects of civil rights. The article also analyzes the interaction of intellectual property law norms and sub-branches of civil law: law of obligations, inheritance law. As you know, obligations are divided into contractual and non-contractual. In the field of intellectual property, contracts are important because they serve as the basis for the emergence, modification and termination of legal relations regarding intellectual property objects. Some provisions of the article are devoted to the analysis of intellectual property rights with the institute of non-contractual obligations. Often, the creation of intellectual property objects is the subject of competitive obligations, and copyright holders may be harmed as a result of torts. Exclusive rights also act as the subject of inheritance and inheritance law, exclusive rights can be the subject of hereditary legal relations, which is also reflected in the content of the article. The issues of interaction of intellectual property law with private international law are touched upon, since intellectual property law is one of the institutions of private international law, which provides for conflict-of-laws regulation of relations complicated by a foreign element. The uniqueness of intellectual property law is also manifested in connection with labor law, since the subject of interaction is relations regarding official works and inventions, which, as a rule, are determined by an employment contract, but require compliance with special legislation of the Republic of Kazakhstan. The article analyzes the interaction of intellectual property law with family law, since exclusive rights and intellectual property objects, being property, can be the subject of family legal relations. The aspects of the interaction of intellectual property law with business law are studied, this is based on the norms on commercialization, support of industrial activity, etc. Keywords: law, intellectual property, inheritance, entrepreneurial activity, innovation, interaction, contractual obligations, competition, state technological policy.